Lex Heerma van Voss , Els Hiemstra-Kuperus, Elise van Nederveen Meerkerk (επιμ.), The Ashgate Companion to the History of Textile Workers, 1650-2000, Farnham, Ashgate 2010 - ΠΑΠΑΣΤΕΦΑΝΑΚΗ ΛΗΔΑ (Μνήμων, 2012)
Δεν παρατίθεται περίληψη.